Direito. biotecnologia e propriedade intelectual: acesso, apropriação e proteção jurídica dos elementos da biodiversidade Amazônica - Stefanello, Alaim Giovani Fortes (2007)
This work aims at studying how the appropriation of the biodiversity elements, particularly those in the Amazon region, and what are the juridical implications arising from such an appropriation. The access to the biodiversity genetic resources, which may result in the achievement of a private property following patent registration, chiefly after the identification and isolation of the active principle of plants and animal with pharmacological potential will be analyzed. In order to achieve this, a study will be carried out on both national and international legislation dealing with intellectual property and access to the traditional knowledge associated to genetic resources. The traditional communities and indigenous societies are major agents within this context, since they own knowledge on the use of nature and its medicinal-purpose applications. The forest, in a wide sense, represents a source of life for such populations, both in the physical and in the spiritual aspect, particularly in the Amazon region, the stage for the greatest world socio-biodiversity and the target for international greed. The regional biological and cultural richness causes the Northern countries to invest against the Southern countries, since the former own biotechnological resources, but only the latter are holders of abundant biological resources. This generates a mutually asymmetric dependence relationship owing to the perverse way on how this relationship is carried out, wrapping up the work as proposed by this study. Keyword: Intellectual Property Rights. Socio-environmental Function of Property. Environmental Law. Biotechnology.